Relationship of Family Experience with the Acceptance of Family Members Who Have Mental Disorders - Aszrul AB; Fatmawati; Fitria Syam (Comprehensive Health Care, 2018)
Mental disorders are disorders that affect one or more functions of the soul that are characterized by disruption of emotions, thought processes, behaviors, and perceptions (sensory capture). This mental disorder causes stress and suffering for sufferers and their families. The family is the closest unit to a family member who has a mental disorder and is the "Main Nurse" for the client. The family plays a role in determining the way or nursing care required by the client. This study aims to determine the relationship of family experience with family acceptance of family members who have mental disorders. The design of this study is qualitative, using a cross-sectional approach. The sample selection in this study was carried out using the Slovin formula so that 52 respondents were identified. The instrument used was a questionnaire. The results of this study indicate that the results obtained value of P = 0.01 where the value of P <0.05 and r = 0.827, it means that there is a strong relationship or correlation between family acceptance with family experience of families with mental disorders in Ujung Loe Health Center Bulukumba Regency. The relationship between family acceptance and family experience can be seen that family experience of families with mental disorders in Ujung Loe Health Center, Bulukumba District is known from the level of family experience that shows 6 families have a good experience, 46 families have a poor experience and none of the respondents in the good category. While the level of family acceptance is 3 (6%), the level of acceptance is good, 49 families the level of acceptance is quite good. The results of this study can be concluded that good family acceptance is closely related to the formation of family experiences on mental disorders. The results of this study also indicate that the higher the family experience, the greater the self-acceptance that will form in the client.